2016
DOI: 10.1007/s12035-015-9674-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Apolipoprotein E (ApoE) Fragmentation Is Linked to Amyloid Pathology in Transgenic Mouse Models of Alzheimer’s Disease

Abstract: The epsilon 4 allele of the apolipoprotein E (ApoE4) gene is the most important risk factor implicated in Alzheimer's disease (AD) etiology. ApoE4 is more susceptible to proteolysis, and ApoE fragments have been shown to promote tau hyperphosphorylation and exert neurotoxic properties. While a plethora of studies deals with the effect of ApoE and its fragments on amyloid-β peptide (Aβ) deposition and clearance, it is largely unknown whether Aβ in turn influences human or murine ApoE expression and its proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…They could show that neuronal ApoE, especially ApoE4, is undergoing proteolytic processing which result in C-terminal truncated fragments that cause cytoskeletal changes (Huang and Mahley, 2014). Moreover, it could be shown that intracellular ApoE fragmentation is especially linked to amyloid pathology as in brains of AD mouse models and patients with AD (Huang et al, 2001; Saul and Wirths, 2017). Alternatively, Theendakara et al (2016) demonstrated that ApoE might also function as a transcription factor in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…They could show that neuronal ApoE, especially ApoE4, is undergoing proteolytic processing which result in C-terminal truncated fragments that cause cytoskeletal changes (Huang and Mahley, 2014). Moreover, it could be shown that intracellular ApoE fragmentation is especially linked to amyloid pathology as in brains of AD mouse models and patients with AD (Huang et al, 2001; Saul and Wirths, 2017). Alternatively, Theendakara et al (2016) demonstrated that ApoE might also function as a transcription factor in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…APOE plays a crucial role in modulating neuronal repair, remodeling, and protection after CNS trauma and disease (Yin et al, 2012 ; Saul and Wirths, 2017 ; Teng et al, 2017 ). During nerve regeneration, APOE is involved in the mobilization and reutilization of myelin-derived cholesterol for axon repair (Mahley, 1988 ; Li et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in presynaptic and postsynaptic proteins in HP and CX contribute to altered functional connectivity, suggesting (67,348,349); TBSX-apoE: in TBSX extraction fraction by ELISA (67). APP processing: APP, BACE, C-terminal fragments by Western blot (49,52,53,58,67,222,329,336,337,339,(348)(349)(350)(351)(352). Neurotrophic factors: brain-derived neurotrophic factor (BDNF) and pCREB proteins by Western blot or mRNA by qPCR (55,61,336,350,352,353).…”
Section: Apoe Modulated Ad Symptoms Exhibited In Efad Micementioning
confidence: 99%